Classification, Community and Sovereignty: Beyond the Individualistic Foundation of Animals Rights [Clasificación, Comunidad y Soberanía: Más Allá de la Fundamentación Individualista de Los Derechos de Los Animales] - Neira-Barrera, H (Universidade do Vale do Rio dos Sinos, 2016)
The debate about how to keep juridical relations with the barbarians in the political philosophy of Plato and Aristotle and, later, the post scholastic debate about Native Americans during the 16th century might become an inspiration for understanding that the main relation with animals is both an epistemological and a political option. Human beings classify the other living beings in order to keep a relation with them. It is possible to classify animals as members of social groups, even similar to states. An ius animalium which classifies animals as members of organized political societies might open the doors to a better relation with animals, even in case of conflict, surpassing the individualistic foundation of animal rights.
Keywords: zoophilosophy; juridical relations with animals; ius animalium; animal rights; Francisco de Vitoria